Effect of varying pCO2 on bacterial activities in tropical coastal and estuarine waters / Nurul Fitrah Mohd Ariffin Marican - Nurul Fitrah , Mohd Ariffin Marican (2019)
The rise of pCO2 levels in oceanic surface waters may have a potential effect on marine bacteria although experimental results related to the effects of pCO2 on marine microbes are rather inconsistent and at times conflicting. In the present study, we investigated (i) the temporal variation of pCO2 and (ii) the effect of elevated pCO2 in seawater on bacterial production (BP), bacterial respiration (BR) and bacterial growth efficiency (BGE) at two different locations which are Port Klang and Port Dickson. Estimated pCO2 in the estuary and coastal water ranged from 345 to 5365 μatm and 421 to 1283 μatm respectively. A total of six sets of experiment were conducted for each location with different concentrations of pCO2 ranging from 305 to 10255 μatm. Estimates of bacterial production and bacterial respiration obtained ranged between 0.06 to 1.21 μM C h-1 and 0.18 to 10.05 μM O2 h-1, respectively. Bacterial growth efficiency was calculated as bacterial production/ (bacterial production + respiration) and ranged from 0.09 to 0.70. pCO2 and bacterial growth efficiency were significantly correlated (r2 = 0.25, P < 0.001, n = 60). The result from this experiment suggested that an increase in atmospheric CO2 might affect BGE, and may have implications towards understanding the ocean carbon flux.